2000
DOI: 10.1046/j.1439-0442.2000.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acid Pattern during the First Month of Life in Calves Fed the First Colostrum at 0–2 h or at 24–25 h after Birth

Abstract: Calves are born with a mostly inadequate essential amino acid (EAA) status. Studies were designed to test the hypothesis that delaying the intake of the first colostrum for 24 h, besides its early effects, also has late effects on plasma free amino acid levels and on the protein status. There were marked and rapid elevations (within 2 h) of plasma levels of various amino acids, and especially of EAA, after the intake of the first colostrum, whereas changes after the intake of mature milk on day 28 of life were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 28 publications
8
29
0
Order By: Relevance
“…The delayed colostrum intake caused metabolic and endocrine changes, as decribed in previous studies (Blum et al., 1997; Hadorn et al., 1997) and for this experiment (Hammon et al. 2000; Zanker et al. 2000a, b; Zanker, Hammon and Blum, unpublished observations).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The delayed colostrum intake caused metabolic and endocrine changes, as decribed in previous studies (Blum et al., 1997; Hadorn et al., 1997) and for this experiment (Hammon et al. 2000; Zanker et al. 2000a, b; Zanker, Hammon and Blum, unpublished observations).…”
Section: Discussionsupporting
confidence: 74%
“…As a consequence, delaying colostrum intake can markedly affect the immune, metabolic, endocrine and nutritional status and growth performance in neonatal calves (Blum et al., 1997; Hadorn et al., 1997; Hammon et al. 2000; Zanker et al. 2000a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our studies, after intake of colostrum there is a rise of blood plasma concentrations of IgG 1 , Lf, total protein, albumin, essential amino acids and an impressive decrease of the glutamine/glutamate ratio. Plasma urea concentrations increase if high amounts of colostrum are fed and plasma glucose concentrations increase with a delay of several days; additionally there is a rise of plasma lipids (triglycerides, phospholipids‐lipids, total cholesterol and essential fatty acids) and of β ‐carotene, vitamins A and E. On the other hand, there are no marked or immediate changes of minerals or plasma concentrations of creatinine, lactate and nitrate (Ronge and Blum, 1988; Blum et al., 1997,2001; Hadorn et al., 1997; Hadorn and Blum, 1997; Egli and Blum, 1998; Hammon and Blum, 1998b, 1999; Hammon et al., 2000, 2002; Kühne et al., 2000; Zanker et al., 2000a,b, 2001a,b; Nussbaum et al., 2002; Schiessler et al., 2002; Muri et al., 2005). Because many other substances, especially proteins and peptides (Michanek and Ventorp, 1989) besides IgG 1 are absorbed intestinally and appear in the circulation (as shown for Lf even in the cerebrospinal fluid of neonatal calves) (Harada and Takeuchi, 2002; Talkuder et al., 2003), functional effects can be expected.…”
Section: Components Of Colostrummentioning
confidence: 99%
“…During the first week of life major changes in blood levels of hormones that are in part associated with nutrition typically occur, such as shown for PRL, adrenocorticotrophic hormone (ACTH), GH, IGFs (and their binding proteins 1–3), insulin, glucagon, leptin, thyroxine (T 4 ), T 3 and cortisol (Ronge and Blum, 1988; Ohta and Sasaki, 1989; Grütter and Blum, 1991a,b; Baumrucker and Blum, 1994; Baumrucker et al., 1994b; Kinsbergen et al., 1994; Skaar et al., 1994; Hadorn et al., 1997; Hadorn and Blum, 1997; Egli and Blum, 1998; Hammon and Blum, 1997a,b,1998a,b,1999; Hammon et al., 2000; Kühne et al., 2000; Rauprich et al., 2000a,b; Bittrich et al., 2002; Nussbaum et al., 2002; Schiessler et al., 2002; Sauter et al., 2003; Zanker et al., 2000a,b,2001a,b; Sparks et al., 2003; Blum et al., 2005). Insulin and IGF‐1 are barely absorbed in the intestine in neonatal calves, even when administered in pharmacological amounts (Baumrucker and Blum, 1994; Grütter and Blum, 1991a; Hammon and Blum, 1997b; Vacher et al., 1995), as in neonatal pigs.…”
Section: Components Of Colostrummentioning
confidence: 99%
“…The time-point of feeding ®rst colostrum is well known to be of up most importance. Thus, in neonatal calves the absorption in the small gut of colostral proteins, such as immunoglobulins (especially immunoglobulin G) and c-glutamyltransferase, is largely limited to day 1 of life (STOTT et al 1979a, b, c;MICHANEK et al 1989;BAUMRUCKER et al 1994a 1 ; HADORN and BLUM 1997;ZANKER et al 2000b). It has also been shown that the status of essential fatty acids and of b-carotene, retinol and a-tocopherol depends on feeding ®rst colostrum within the ®rst 24 h of life ZANKER et al 2000c).…”
Section: Introductionmentioning
confidence: 99%